Developmental origins of cognitive offloading. Issue 1928 (10th June 2020) - Armitage, Kristy L.; Bulley, Adam; Redshaw, Jonathan
Abstract : Many animals manipulate their environments in ways that appear to augment cognitive processing. Adult humans show remarkable flexibility in this domain, typically relying on internal cognitive processing when adequate but turning to external support in situations of high internal demand. We use calendars, calculators, navigational aids and other external means to compensate for our natural cognitive shortcomings and achieve otherwise unattainable feats of intelligence. As yet, however, the developmental origins of this fundamental capacity for cognitive offloading remain largely unknown. In two studies, children aged 4–11 years ( n = 258) were given an opportunity to manually rotate a turntable to eliminate the internal demands of mental rotation––to solve the problem in the world rather than in their heads. In study 1, even the youngest children showed a linear relationship between mental rotation demand and likelihood of using the external strategy, paralleling the classic relationship between angle of mental rotation and reaction time. In study 2, children were introduced to a version of the task where manually rotating inverted stimuli was sometimes beneficial to performance and other times redundant. With increasing age, children were significantly more likely to manually rotate the turntable only when it would benefit them. These results show how humans gradually calibrate their cognitive offloading strategies throughout childhood and thereby uncover the developmental origins of this central facet of intelligence.